Androgen regulation of host defenses and response to inflammatory stimuli in the prostate gland - Quintar, Amado Alfredo (2017)
The prostate gland is a strictly androgen-dependent organ which is also the main target of infectious and inflammatory diseases in the male reproductive tract. Host defenses and immunity of the gland have unique features to maintain a constant balance between response and tolerance to diverse antigens. In this context, the effects of reproductive hormones on the male tract are thus complex and have just started to be defined. From the classical description of “the prostatic antibacterial factor,” many host defense proteins with potent microbicidal and anti-tumoral activities have been described in the organ. Indeed, it has been proposed a central role for resident cells, that is, epithelial and smooth muscle cells, in the prostatic response against injuries. However, these cells also represent the target of the inflammatory damage, leading to the development of a Proliferative Inflammatory Atrophy-like process in the epithelium and a myofibroblastic-like reactive stroma. Available data on androgen regulation of inflammation led to a model of the complex control, in which the final effect will depend on the tissue microenvironment, the cause of inflammation, and the levels of androgens among other factors. In this paper, we review the current scientific literature about the inflammatory process in the gland, the modulation of host defense proteins, and the influence of testosterone on the resolution of prostatitis.